Juridical Analysis of Legal Sanctions for Criminal Acts of Corruption Conducted Together (Study of Supreme Court Decision Number 1054 K/Pid.Sus/2019) - Asor Olodaiv Siagian; Alpi Sahari; Ida Nadirah (International Journal Reglement & Society (IJRS), 2022)
Cases of criminal acts of corruption were carried out jointly based on the study of the Supreme Court's decision Number 1054 K/Pid.Sus/2019. The Defendant Luanna Wiriawaty as Director of PT Djaya Bima Agung who was appointed as the winner of the auction for the Procurement of KB II Batang Three-Year implants Plus Inserter T.A 2014 at the Directorate of Family Planning Health Development through the Government Line at the Deputy for Family Planning and Reproductive Health BKKBN, together with witness Yenny Wiriawaty as President Director of PT Triyasa Nagamas Farma as well as shareholder of PT Djaya Bima Agung and witness Karnasih Tjiptaning, S. Kom., MPH as Commitment Making Officer (each is subject to separate prosecution). This study aims to examine the regulation of criminal acts of corruption that are carried out together based on the applicable legal provisions in Indonesia. To examine the mechanism of reverse evidence in the crime of corruption and to analyze juridically the legal sanctions for the crime of corruption carried out together with the decision of the Supreme Court Number 1054 K/Pid.Sus/2019. This research method uses normative research with data types consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results of this study the Supreme Court has mistakenly applied article 2 paragraph (1) to the defendant in the aquo case, in the author's opinion the difference between article 2 and article 3 of Law 31 of 1999 concerning the Crime of Corruption, namely in Article 3, the perpetrator can be charged if has the authority, while in Article 2, everyone referred to in the article is broader and more general. Furthermore, judex juris was wrong by not applying Article 64 of the Criminal Code